2015
DOI: 10.1021/jf505277e
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-gallate Inhibits Fibrillogenesis of Chicken Cystatin

Abstract: Previous studies have reported that (-)-epigallocatechin-3-gallate (EGCG), the most abundant flavonoid in green tea, can bind to unfolded native polypeptides and prevent conversion to amyloid fibrils. To elucidate whether this antifibril activity is specific to disease-related target proteins or is more generic, we investigated the ability of EGCG to inhibit amyloid fibril formation of amyloidogenic mutant chicken cystatin I66Q, a generic amyloid-forming model protein that undergoes fibril formation through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Curcumin and kaempferol have also been suggested to have similar π-π interactions with this residue [ 19 ]. The fact that taxifolin has displayed a binding to the aggregation-prone HEWL β-domain has also been reported in previous studies investigating other polyphenols, including myricetin [ 18 ], curcumin [ 19 , 58 ], kaempferol [ 19 ], quercetin, and resveratrol [ 59 ]. Interestingly, the interaction with Asn59 and Trp62 in the aggregation-prone β-domain of HEWL could explain the conformational changes detected by anisotropy measurement( Table 3 ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Curcumin and kaempferol have also been suggested to have similar π-π interactions with this residue [ 19 ]. The fact that taxifolin has displayed a binding to the aggregation-prone HEWL β-domain has also been reported in previous studies investigating other polyphenols, including myricetin [ 18 ], curcumin [ 19 , 58 ], kaempferol [ 19 ], quercetin, and resveratrol [ 59 ]. Interestingly, the interaction with Asn59 and Trp62 in the aggregation-prone β-domain of HEWL could explain the conformational changes detected by anisotropy measurement( Table 3 ).…”
Section: Resultssupporting
confidence: 65%
“…There are many reports demonstrating that polyphenols are effective inhibitors of protein fibrillation [ 12 , 13 , 17 20 ], through interaction with one or more of the amyloidogenic species, produced during the course of the aggregation process. For instance, some polyphenols prevent amyloid formation by interacting with and stabilizing native structure of proteins [ 47 , 58 , 61 ]; while others bind to prefibrillar structures and redirect amyloidogenic polypeptides into unstructured, off-pathways oligomers [ 62 ], or toward an alternative non-toxic disordered (amorphous) aggregation pathway [ 20 ]. Recently, Hirohata et al .…”
Section: Resultsmentioning
confidence: 99%
“…Further addition of vitamin k3 to preformed HEWL amyloid fibrils did not lead to decrease in ThT fluorescence intensity, it suggests that vitamin k3 cannot reverse the fibril formation but can only inhibit its formation. These results revealed that vitamin k3 inhibits fibrillation from very beginning of log phase as observed in the case of EGCG which inhibits fibrillogenesis of Chicken Cystatin 29 .…”
Section: Resultsmentioning
confidence: 55%
“…TEM is generally used to observe and prove the morphology of aggregates qualitatively (Wang et al 2015;Sun et al 2016). TEM images in Fig.…”
Section: Morphologies Of As Aggregatesmentioning
confidence: 99%